32 THE RELATIONSHIP OF SYSTOLIC BLOOD PRESSURE, HIGH-DENSITY LIPOPROTEIN AND GLUCOSE CONTROL IN SOUTH ASIAN INDIAN IMMIGRANTS. (1st March 2005) - Rosewater, I. G.; Caputo, D.; Farooki, A.; Amorosa, L. F.
Abstract : We have previously noted that a self-selected study sample of South Asian Indian immigrants with a unique predominance of older men demonstrates a high prevalence of fasting hyperglycemia, which negatively correlates with their HDL. To further develop the health profile of this emerging minority, we are reporting on their systolic blood pressure (sBP), and its relationship to HDL and glucose control. The sample includes age-matched males (n = 63) and females (n = 44) with average age of 64 and FSG of 125 mg/dL. Their mean BMI is 25. Subjects in the study sample have been living in the USA for a mean of 12 years. Because of the high mean fasting serum glucose, the study sample was stratified into 3 glycemic groups: N = (FSG<100 mg/dL and A1C<6.4%); I = (FSG ≥ 100 and<126, A1C<6.4); D = (FSG ≥ 126 and A1C ≥ 6.4). Fasting blood glucose across all glycemic groups correlated with A1C, r = .8 (p<0.01). Mean HDL (Figure 1 ) was higher in women across all groups, p<0.01, and significantly declined with increasing hyperglycemia. For both genders HDL correlated with triglycerides (TRG), sBP and FSG (r = -0.4, -0.3, -0.3, p<0.01, respectively). Despite the trend shown in Figure 2, marked variations in TRG precluded a significant change in mean TRG between sexes and glycemic groups. Mean sBP demonstrated an exact reciprocal pattern compared to HDL, increasing with hyperglycemia in both sexes (p<0.01). The data show that in this homogenous ethnic group, dyslipidemia and systolic hypertension are a continuum of the molecular defects relating glucose and lipid control to blood pressure regulation. Figure 2 : HDL (mg/dL). Figure 3 : TRG (mg/dL). Figure 3 : sBP (mm Hg).